2019
DOI: 10.1021/acs.jpcc.9b10457
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Optical Properties of Lead-Free 2D Tin-Based Perovskites with Carbon Chain Spacers

Abstract: We prepare a series of two-dimensional (2D) tin-based perovskite (RNH 2 ) 2 SnBr 4 with different carbon chains. All of them have extra-large Stokes shifts, broad emission, and ultralong PL lifetimes. The PLQYs of (C 8 H 17 NH 2 ) 2 SnBr 4 and (OAm) 2 SnBr 4 powders reach up to 54 and 60%, respectively. Density functional theory calculations and experimental results reveal that the properties of 2D Sn-based perovskites may originate from self-trapped excitons, which result from excited-state structural deforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…Therefore, we assumed that there were some non-ignorable non-radiative carrier trapping processes, which leaded to its lowest PLQY. 28,[41][42][43] The differences of PLQY and lifetime among these (RNH 3 ) 2 SnBr 4 indicated that the optical properties were influenced by the distortion of the structure.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Therefore, we assumed that there were some non-ignorable non-radiative carrier trapping processes, which leaded to its lowest PLQY. 28,[41][42][43] The differences of PLQY and lifetime among these (RNH 3 ) 2 SnBr 4 indicated that the optical properties were influenced by the distortion of the structure.…”
Section: Resultsmentioning
confidence: 98%
“…S2. An obvious peak at 284 eV was related to C 1s; the peak of 400.9 eV was attributed to N 1s; the peaks located at 485.8 eV and 494.1 eV originated from Sn 3d of Sn 2+ ion; 26,28 the peak located at 67.5 eV was attributed to Br 3d. 35 According to integrated peak intensities, the elemental of the 2D (C 8 H 17 NH 3 ) 2 SnBr 4 perovskites ratio of N : Sn : Br was 4.4 : 1 : 5.6.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations